EFFECT OF SUPPLEMENTATION OF WHEAT BRAN ON THE PRODUCTION OF SHIITAKE (LENTINUS EDODES (BERK) PEGLAR) USING WHEAT STRAW AND SAW DUST SUBSTRATES - SHARMA, SHIVANI; K. KHANNA , PARDEEP; KAPOOR, SHAMMI (The Bioscan, 2013)
Lentinus edodes (Berk.) Peglar, the shiitake mushroom, is worldwide one of the most widely cultivated mushrooms. The cultivation of edible mushrooms is a biotechnological process that uses various residues to produce food of high nutritional value which can be a solution to problems of global importance, such as the lack of protein in developing countries and the possibility of environmental management. Five different strains of Lentinus edodes (LeS, OE-38, OE-142, OE-329 and OE-388) were cultivated on wheat straw and saw dust and spawn run time, weight of fruit bodies and biological efficiency were recorded. Wheat straw substrate produced maximum biological efficiency in OE-388 (66.8%) and OE-329 (46.2%) strains. Ten percent supplementation of wheat bran was the best among all the supplements tried. However, in case of sawdust substrate, maximum biological efficiency was obtained at 5 per cent level of wheat bran supplementation in LeS, OE-142, OE- 388 strains. The days for spawn run were also less in wheat straw substrate as compared to saw dust substrate.